Before the country : native renaissance, Canadian mythology - McKenzie, Stephanie (University of Toronto Press, 2007)
"In the late 1960s and early 1970s, Canada witnessed an explosion in the production of literary works by Aboriginal writers, a development that some critics have called the Native Renaissance. Before the Country explores the extent to which this body of literature exposed the fallacies of one specific story, or non-Native national myth, that had been developed at an early date in Canada." "In the context of Northrop Frye's theories of myth, and in light of the attempts of social critics and early anthologists to define Canada and Canadian literature, Stephanie McKenzie suggests ways in which stories react to one another. She examines anew the aesthetics of Native literature and, in a style that is as creative as it is scholarly, incorporates the principles of storytelling into the unfolding of her argument. This strategy not only enlivens her narrative, but also underscores the need for new theoretical strategies in the criticism of Aboriginal literatures. Before the Country invites us to engage in one such endeavour."--Jacket.